Hubungan Gaya Hidup dengan Kesehatan Mental Remaja di Indonesia (Analisis Data Global School-Based Student Health Survey Indonesia 2015) - Silfia Dini Pratiwi; Ratna Djuwita (Jurnal Epidemiologi Kesehatan Komunitas, 2022)
Background: Mental health disorders are one of the main risk factors for causing pain and death in adolescents. Symptoms of mental health disorders can be anxiety, depression, sleep disorders, suicidal or self-harm ideas and attempted suicide. Poor mental health is a severe health problem, especially in adolescents. Mental health is affected by multiple factors, including daily behavior and individual lifestyle.Methods: This study aimed to find out the relationship between lifestyle and mental health of adolescent in Indonesia. This study used secondary data of Indonesia's Global School-Based Student Health Survey in 2015. The population of this study was 9.628 students aged 11-18 years in Indonesia. This research sample was obtained by total sampling method. This study used multivariate analysis of cox regression and large associations expressed with Prevalence Ratio (PR) with 95% Confidence Interval.Result: The prevalence of adolescents in Indonesia with mental health disorders is 9,4%. Multivariate analysis test results showed there was a significant relationship between lifestyle and adolescent mental health in Indonesia (PR= 1,47, 95% CI: 1,31 – 1,65) after being controlled by gender, socioeconomic status, and bullying.Conclusion: The school and parents are advised to work together to prevent mental health disorders in adolescents.